Factor completely, then place the factors in the proper location on the grid.
3y4 - 2y2 - 5

3y^4 - 2y^2 - 5; = 3y^4 - 5y^2 + 3y^2 - 1*5 = (3y^2 - 5)(y^2 + 1)

Question|Asked by little.green.dalek

Asked 4/4/2016 5:46:11 PM

Updated 4/8/2016 11:22:17 PM

1 Answer/Comment

Flagged by Venen [4/8/2016 11:01:47 PM], Unflagged by jeifunk [4/8/2016 11:22:11 PM], Edited by jeifunk [4/8/2016 11:22:17 PM]

Rating

3

3y^4 - 2y^2 - 5;

= 3y^4 - 5y^2 + 3y^2 - 1*5

= (3y^2 - 5)(y^2 + 1)

= 3y^4 - 5y^2 + 3y^2 - 1*5

= (3y^2 - 5)(y^2 + 1)

Added 4/8/2016 11:02:31 PM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [4/8/2016 11:22:23 PM]

Multiply the following polynomials, then place the answer in the proper location on the grid. Write the answer in descending powers of a.
(a - 6)(a 2 +6a + 36)
**Weegy:** 3-3 = 0 (More)

Question|Asked by little.green.dalek

Expert Answered

Updated 3/30/2016 9:45:52 PM

1 Answer/Comment

(a - 6)(a^2 +6a + 36)

=a^3 + 6a^2 + 36a - 6a^2 - 36a - 216

=a^3 - 216

=a^3 + 6a^2 + 36a - 6a^2 - 36a - 216

=a^3 - 216

Added 3/30/2016 9:45:51 PM

This answer has been confirmed as correct and helpful.

Factor completely, then place the answer in the proper location on the grid.
49x 2 + 42xy + 9y 2

Question|Asked by little.green.dalek

Not Answered

Updated 3/30/2016 8:57:19 PM

1 Answer/Comment

Place the indicated product in the proper location on the grid.
(b2 + 8 )(b2 - 8)

Question|Asked by little.green.dalek

Expert Answered

Updated 4/4/2016 8:59:00 PM

1 Answer/Comment

(b2 + 8 )(b2 - 8)

=b4 - 8b2 + 8b2 - 64

=b4 - 64

=b4 - 8b2 + 8b2 - 64

=b4 - 64

Added 4/4/2016 8:58:50 PM

This answer has been confirmed as correct and helpful.

Factor completely, then place the factors in the proper location on the grid.
b2 - 7b + 12
**Weegy:** b^2 - 7b + 12 is = (b - 3)(b - 4) (More)

Question|Asked by little.green.dalek

Expert Answered

Updated 4/4/2016 9:00:18 PM

0 Answers/Comments

Factor completely, then place the factors in the proper location on the grid.
a2 - 5a - 6
**Weegy:** a^2 - 5a - 6 = (a + 1)(a - 6) (More)

Question|Asked by little.green.dalek

Expert Answered

Updated 4/4/2016 9:05:03 PM

0 Answers/Comments

27,959,726

questions answered

There are no comments.